ACCUMULATION OF HEAVY METAL IN CHINESE WATERCHEST-NUT (Eleocharis dulcis Burm.f.) Trin. Ex Hensch.) IN PHYTOREMEDIA-TION OF COAL ACID MINE WATER ON CONSTRUCTED WETLANDS. - Juswardi, Juswardi; Tanzerina, Nina; Junaidi, Endri (BIOVALENTIA: Biological Research Journal, 2023)
The coal open mining is an activity that has an impact on the environment, including acid mine drainage (AMD). The management of AMD can be done by phytoremediation using Chinese Waterchestnut (Eleocharis dulcis Burm.f.) Trin. ex Hensch.) on system of constructed wetlands (CWs). So the research was carried out with the aim of evaluation the accumulation of heavy metals iron (Fe) and Manganese (Mn) which were absorbed in E. dulcis in constructed wetlands system at WTP Air Laya PT. Bukit Asam. The accumulation of Fe in the roots of E. dulcis was 986.42 ppm (w/w) while the accumulation of Fe in the leaves was 392.22 ppm (w/w). The accumulation of Mn in the roots of E. dulcis was 24.49 ppm (w/w), while the accumulation of Mn in the shoots was 96.83 ppm (w/w). E. dulcis is known to have the potential to increase AMD pH and reduce levels of Fe, Mn and SO42- so that it can meet the quality standards of coal mining activity wastewater. The accumulation of Fe and Mn in the roots and shoots of E. dulcis and on AMD can be used as an effort to monitor the success of AMD phytoremediation on Constructed Wetlands system at WTP Air Laya.